2020
DOI: 10.1111/jog.14441
|View full text |Cite
|
Sign up to set email alerts
|

Missing decidual Doppler signals as a new diagnostic criterion for placenta accreta spectrum: A case described using superb microvascular imaging

Abstract: We present a case of a 34‐year‐old pregnant woman with a prior cesarean delivery presenting with placenta previa. Placenta previa accreta was diagnosed from missing decidual flow signals using superb microvascular imaging (SMI). At 31 weeks' gestation, B‐mode ultrasonography showed that the placenta was attached to the anterior uterine segment, extending over the internal cervical os. In normally appearing myometrium, SMI demonstrated double layers of flow signals underneath the placental basal plate, correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The decidua plays a fundamental role in the interaction between the uterus and the placenta. Abnormal decidual development is related to early fetal loss and increases the risk of an abnormally invasive placenta [10][11][12][13] . Three layers of the decidua have been described: (1) decidua basalis, located at the site of placental insertion; (2) decidua capsularis, surrounding the gestational sac; and (3) decidua parietalis, which is not in contact with the embryo 14,15 .…”
Section: Decidual Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The decidua plays a fundamental role in the interaction between the uterus and the placenta. Abnormal decidual development is related to early fetal loss and increases the risk of an abnormally invasive placenta [10][11][12][13] . Three layers of the decidua have been described: (1) decidua basalis, located at the site of placental insertion; (2) decidua capsularis, surrounding the gestational sac; and (3) decidua parietalis, which is not in contact with the embryo 14,15 .…”
Section: Decidual Blood Flowmentioning
confidence: 99%
“…In late gestation, this hypoechoic area can be mistaken for an abruption; however, directional color imaging and power Doppler ultrasound show a rich maternal vascular component with very low resistance (Figure 4) 17 . Reduced or absent decidual blood flow can be associated with an abnormally invasive placenta 13 . More studies on decidual perfusion/circulation are needed.…”
Section: Normal Placental Circulationmentioning
confidence: 99%
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
“…After exclusion of duplicates and two articles that were not available, 880 remained, of which a further 793 were excluded after screening the titles and abstracts, as the data they reported were not relevant. The remaining 87 studies were retrieved for full-text review, of which 72 were excluded after in-depth review, leaving 15 studies describing eight new ultrasound signs for the prenatal evaluation of PAS [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The process of selection of these articles is summarized in Figure S1, and the characteristics of the 15 studies identified by the systematic review are presented in Table S1.…”
Section: Literature Searchmentioning
confidence: 99%
“…In recent years, some authors have begun to apply SMI Doppler in obstetrics to evaluate placental microvasculature proving the potential of this technique in the obstetrics field [10][11][12][13]. Although investigation in this field is still scarce, recent studies have been published applying this technique to assess fetal organs [20,21] or placental anomalies such as the placenta accreta spectrum [22,23]. With regard to pla- cental vasculature, hitherto most studies have focused on describing the observations made by explores, but it was not until the study made by our group, that objective quantitative values were described for normal placentas.…”
Section: Discussionmentioning
confidence: 99%